Karakterisasi Pati yang Dimodifikasi dari Batang Sawit dengan Perbedaan Suhu Hidrolisis - Salsabila, Ghea Patika; Raja, Pada Mulia (Jurnal Ilmiah Pangan Halal, 2026)
Oil palm trunks are waste products from plant rejuvenation that can be another source of starch. This study aims to examine how the temperature of acetic acid hydrolysis affects the properties of starch from oil palm trunks. The method used was a nonfactorial Completely Randomized Design (CRD) with three variations of hydrolysis temperatures, namely 40°C, 45°C, and 50°C, each repeated three times. The parameters observed included moisture content, ash content, amylose content, amylopectin content, and functional groups with the help of FTIR. Data were analyzed using ANOVA at the 5% level. The results of this study indicate that the hydrolysis temperature affects the properties of starch. A temperature of 40°C produces the lowest moisture content of 10.16%, while a temperature of 45°C produces the highest amylose content of 13.43% and the lowest amylopectin content of 86.56%. Treatment at 50°C shows a decrease in starch quality due to structural damage during the hydrolysis process. The FTIR analysis results showed the presence of typical starch functional groups such as O–H, C–H, and C–O–C in all treatments. The results of the study showed that a hydrolysis temperature of 45°C was the best treatment for obtaining oil palm stem starch with the best properties.